Identification of Five Cytotoxicity-Related Genes Involved in the Progression of Triple-Negative Breast Cancer - Zhang, Yan; Tong, Gui-hui; Wei, Xu-Xuan; Chen, Hai-yang; Liang, Tian; Tang, Hong-Ping; Wu, Chuan-An; Wen, Guo-Ming; Yang, Wei-Kang; Liang, Li; Shen, Hong (Frontiers in genetics, 2022)
Background: Breast cancer is one of the deadly tumors in women, and its incidence continues to increase. This study aimed to identify novel therapeutic molecules using RNA sequencing (RNA-seq) data of breast cancer from our hospital. Methods: 30 pairs of human breast cancer tissue and matched normal tissue were collected and RNA sequenced in our hospital. Differentially expressed genes (DEGs) were calculated with raw data by the R package “edgeR”, and functionally annotated using R package “clusterProfiler”. Tumor-infiltrating immune cells (TIICs) were estimated using a website tool TIMER 2.0. Effects of key genes on therapeutic efficacy were analyzed using RNA-seq data and drug sensitivity data from two databases: the Cancer Cell Line Encyclopedia (CCLE) and the Cancer Therapeutics Response Portal (CTRP). Results: There were 2,953 DEGs between cancerous and matched normal tissue, as well as 975 DEGs between primary breast cancer and metastatic breast cancer. These genes were primarily enriched in PI3K-Akt signaling pathway, calcium signaling pathway, cAMP signaling pathway, and cell cycle. Notably, CD8 + T cell, M0 macrophage, M1 macrophage, regulatory T cell and follicular helper T cell were significantly elevated in cancerous tissue as compared with matched normal tissue. Eventually, we found five genes ( GALNTL5, MLIP, HMCN2, LRRN4CL, and DUOX2 ) were markedly corelated with CD8 + T cell infiltration and cytotoxicity, and associated with therapeutic response. Conclusion: We found five key genes associated with tumor progression, CD8 + T cell and therapeutic efficacy. The findings would provide potential molecular targets for the treatment of breast cancer.